Analisis Penerjemahan Novel “Keledai yang Bijak” dari Novel Berbahasa Arab “Himar Al-Hakim” Karya Taufiq Al-Hakim - Chilwina, Nadhita; Surur, Misbahus (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Studies on translation techniques are still limited, even though this aspect plays a crucial role in producing accurate, acceptable, and understandable translations, especially for language learners. This study aims to describe the forms of translation techniques in the novel "The Wise Donkey," a translation of the Arabic novel "Himar Al-Hakim" by Taufiq Al-Hakim. This study employed a qualitative descriptive method, with primary data sources being the novel "Himar Al-Hakim" and its translation "The Wise Donkey," as well as secondary data from literary theory and translation. Data were collected through reading and note-taking techniques and analyzed using the Miles and Huberman model, encompassing reduction, presentation, verification, and conclusion. Validity was maintained through source triangulation, expert consultation, and rereading of the text. This study presents 95 data points on translation techniques used by translators of the Arabic novel "Himar Al-Hakim." Researchers identified 12 translation techniques in Taufiq Al-Hakim's novel "Keledai yang Bijak," translated by Himar Al-Hakim, including adaptation, borrowing, calque, description, conventional equivalence, and transposition. Each technique has its own characteristics in conveying the meaning of a source language text. Each meaning expressed serves to facilitate understanding of a translated work, ensuring its readability and high level of acceptability. These findings contribute to the study of Arabic-Indonesian literary translation by mapping translation strategies that maintain meaning and aesthetics, and have implications for teaching translation as a practical teaching tool. The limitations of this research open up opportunities for further study of other techniques and their impact on translation quality.